2010
DOI: 10.1016/j.cub.2010.06.074
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Thickness Cue for Cold Sensing in a Bacterium

Abstract: Thermosensors are ubiquitous integral membrane proteins found in all kinds of life. They are involved in many physiological roles, including membrane remodeling, chemotaxis, touch, and pain [1-3], but, the mechanism by which their transmembrane (TM) domains transmit temperature signals is largely unknown. The histidine kinase DesK from Bacillus subtilis is the paradigmatic example of a membrane-bound thermosensor suited to remodel membrane fluidity when the temperature drops below approximately 30°C [1, 4] pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
129
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(150 citation statements)
references
References 22 publications
7
129
0
Order By: Relevance
“…For many bacterial pathogens, an important environmental stimulus is a shift in temperature from vector or environment to the human host. Temperature change has been demonstrated to induce bacterial membrane remodeling and is required for maintenance of optimal membrane architecture (3)(4)(5).…”
mentioning
confidence: 99%
“…For many bacterial pathogens, an important environmental stimulus is a shift in temperature from vector or environment to the human host. Temperature change has been demonstrated to induce bacterial membrane remodeling and is required for maintenance of optimal membrane architecture (3)(4)(5).…”
mentioning
confidence: 99%
“…Some evidence suggests that such changes in membrane thickness may be a key factor in the regulation of DesK sensing and signaling. First, an MS-DesK length mutant (4V) containing four extra valines in the C-terminal region of its transmembrane segment was found to be inactive and to remain locked in the phosphatase state on a decrease in temperature (5). Second, reconstitution studies showed increasing activity of both DesK and MS-DesK with increasing acyl chain length of the lipids in which the protein is reconstituted (5,8).…”
Section: Significancementioning
confidence: 99%
“…Importantly, MS-DesK shows a temperature-dependent switch in activity comparable to the full-length DesK not only in vivo, but also when reconstituted in protein-free lipid bilayers made from bacterial lipids (5). Therefore, no other membrane proteins are involved in sensing or signal transduction.…”
mentioning
confidence: 99%
See 2 more Smart Citations